Investigating math education in reducing math anxiety with the help of Data Envelopment Analysis - Ensieh Khorramian; Mohsen Rostamy-Malkhalifeh; Ahmad Shahvarani (Measurement + Control)
Mathematics is one of the important subjects of a student at various stages. From the past to present, hearing the name of mathematics has been accompanied by fear and anxiety for a significant group of students. Quality of mathematics education is a complex and multifaceted concept, and various authors with different viewpoints have proposed methods regarding the quality. Decision making in the selection of the teaching method is one of the pillars of a teacher and applying proper methods which are appropriate to the educational environment has an effective role in the success of education and reduction of students’ anxiety. In this research, with the help of Network Data Envelopment Analysis (NDEA) and Sexton’s method, we are going to rank several different teaching methods to reduce the math anxiety of second year elementary school students. Several methods were implemented in the classrooms and after that the results were evaluated using the above method and it was found that the game method has the highest rank and based on this research, it will be tried to implement this method in the classroom. Lessons should be used to reduce students’ math anxiety. In this article, we delve into the study of practical scenarios and conditions that may make the utilization of these methods more effective in mathematics education. Additionally, we offer recommendations to teachers and individuals involved in math instruction to maximize the benefits of mathematical education and reduce math anxiety.